Usaha Kaos Sablon Sebagai Wujud UMKM Penopang Ekonomi Keluarga - Danang Sunyoto; Magister Alfatah Kalijaga (jurnal ABDIMAS Indonesia, 2023)
Efforts to improve the community's economy through screen-printed t-shirt businesses. Problem: Implementation of activities still uses manual methods. Literature review and observation of implementation of activities in the field. Result: Screen printing t-shirt business activities need to be changed from the manual method to the modern method (screen printing machine) to increase the income of screenprinting t-shirt entrepreneurs, and there is a need for assistance from the government.